PENGARUH VARIASI ARUS BUSUR LISTRIK PENGELASAN GMAW TERHADAP KEKUATAN IMPAK PADA BAJA KARBON RENDAH ST 37 - Bilal Nur Ikhsan; Rodika Rodika; Yuli Dharta (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
The welding procedure looks very simple but in practice there are many problems that must be overcome where in repairing it requires various kinds of knowledge, electric arc current and welding defects greatly affect the strength of the weld joint. he conducted a study to determine the effect of electric arc current on low carbon steel St 37 on impact strength. The test method was carried out by the charpy method using five (5) variations of amperemeter 160,180,200,220,240 with plate dimensions: 200mm×100mm×10mm and using a single V seam, with a welding position of 1G (groove). GMAW welding method. specimen dimensions 55mm,×10mm,×10mm,. So it can be concluded that the lower the electric arc current, the higher the impact price, and vice versa, the higher the arc current, the lower the impact value. The results of the highest impact value on an electric arc current of 160 from the Capping weld with a value of 0.92778 (Joule/mm²), and the smallest value is found in the result of the Root Pass weld on an electric arc current of 240 with a value of 0.09875 (Joule/mm²) .